Solar‐Driven Nitrogen Fixation Catalyzed by Stable Radical‐Containing MOFs: Improved Efficiency Induced by a Structural Transformation - Hu, Kong‐Qiu; Qiu, Peng‐Xiang; Zeng, Li‐Wen; Hu, Shu‐Xian; Mei, Lei; An, Shu‐Wen; Huang, Zhi‐Wei; Kong, Xiang‐He; Lan, Jian‐Hui; Yu, Ji‐Pan; Zhang, Zhi‐Hui; Xu, Zhong‐Fei; et al. (Angewandte Chemie, 2020)
Herein we present a new viologen‐based radical‐containing metal–organic framework (RMOF) Gd‐IHEP‐7, which upon heating in air undergoes a single‐crystal‐to‐single‐crystal transformation to generate Gd‐IHEP‐8. Both RMOFs exhibit excellent air and water stability as a result of favorable radical‐radical interactions, and their long‐lifetime radicals result in wide spectral absorption in the range 200–2500 nm. Gd‐IHEP‐7 and Gd‐IHEP‐8 show excellent activity toward solar‐driven nitrogen fixation, with ammonia production rates of 128 and 220 μmol h−1 g−1, respectively. Experiments and theoretical calculations indicate that both RMOFs have similar nitrogen fixation pathways. The enhanced catalytic efficiency of Gd‐IHEP‐8 versus Gd‐IHEP‐7 is attributed to intermediates stabilized by enhanced hydrogen bonding. A single‐crystal‐to‐single‐crystal (SCSC) transformation of stable radical‐containing MOF Gd‐IHEP‐7 generates Gd‐IHEP‐8. It is accompanied by a marked increase in efficiency of sacrificial agent‐free photocatalytic nitrogen fixation to yield NH3 from H2O and N2 under simulated solar light irradiation at ambient temperature. The NH3 production rate of 220 μmol h−1 g−1 for Gd‐IHEP‐8 is a new record for MOF photocatalysts.